Analisis Kriteria untuk Perencanaan Program Pemeliharaan Embung Irigasi (Studi Kasus : Embung Haliwen dan Haekrit Kabupaten Belu) - Bria, Melchior (Jurnal Teknik Sipil dan Perencanaan, 2017)
: Â The problem of irrigation dams (small farm reservoair) is functional degradation, characterized by reduced capacity of collected water, sedimentation, seepage, the growth of wild plants in the body of weir / dike, erosion, and some other problems. Therefore, good and sustainable maintenance is required. One of them by determining the right criteria as the basis for planning the maintenance program. The determination of this criterion is based on fact (filling questionnaire) and literature review which then tested the validity and reliability to determine the criteria to be used. Furthermore, the analysis of the various criteria stated valid and reliable. Criteria are determined based on validity, reliability and frequency distribution with the number of procession answers is very important and important> 50%. The results of the analysis indicate influential Criteria and subcriteria namely Structural Stability Criteria (sub criteria: Body Dam, Embung Pool, Spillway, Building Assistance, Water Distribution Network, Condition Value); Physical and Environmental Criteria (subcriteria of Changes in the Natural Span, Rainfall and Evapotranspiration, Soil Structure around Embung, Plague of Plague Around Embung); Financial Criteria / Eknomi (subcriteria of Agricultural Product Result, Economic Value of Emung, Investment Fund); Government Policy Criteria (subcriteria: Spatial Plan, Provision of Maintenance Budget, Water Management, Institutional / Organization Aspect); Socio-Cultural Criteria (subcriteria: Community Participation, Local Wisdom / Customary Law, and Tourism Development)